Match-level uncertainty in professional tennis revisited - a novel approach applied for the time between 2010 and 2019 - Özaydin, S.; Könecke, T. (Journal of Sports Economics, 2024)
Despite its popularity, outcome uncertainty in professional tennis did not receive much attention from academics in the recent past. This is astonishing because it should be of utmost importance in professional tennis in the following years with the approaching end of the era of the Big 3. This study investigates match-level uncertainty in professional women's and men's tennis between 2010 and 2019 using a logit model with a dataset consisting of 51,054 matches. In the different analyses, the variations in the ranking and quality differences between players are taken into account in addition to differences across surfaces, tournaments, and genders. In the investigated period, women's tennis has relatively higher outcome uncertainty when compared to men's. The results also illustrate that talent seems to be distributed more evenly in women's tennis, whereas men's tennis has high heterogeneity in terms of talent. Moreover, very specific subgroups of matches having the highest and lowest uncertainty in men's and women's tennis are identified. Managerial implications are also presented to show how organizers, policy makers and, eventually, fans can benefit from the insights presented in this study.